Impact of conservation agriculture on humic acid quality and clay humus complexation under maize (Zea mays)-wheat (Triticum aestivum) and pigeon pea (Cajanus cajan)-wheat cropping systems - DAS, ABHISHEK; AHMED, NAYAN; PURAKAYASTHA, T J; BISWAS, SUNANDA; RAY, PRASENJIT; SINGH, BINDER; DAS, T K; KUMAR, RAJESH; LAMA, ACHAL (The Indian Journal of Agricultural Sciences, 2023)
An attempt was made to study the humic acid (HA) quality and clay humus complex in order to generate valuable information regarding soil carbon (C) and recalcitrant carbon variations under conservation agriculture (CA) practices. It is worthwhile to mention that CA has got wider acceptance among researchers and farmers nowadays. A field experiment was conducted in an Inceptisol with three treatments, namely conventional tillage (CT), zero tillage (ZT) without residue and zero tillage with residue (ZT+R) in a maize (Zea mays L.)-wheat (Triticum aestivum L.) (M-W) and pigeon pea (Cajanus cajan L.)-wheat (P-W) cropping system at ICAR-Indian Agricultural Research Institute, New Delhi, with a view to characterize the HA by E4/E6 ratio and total acidity, and to specify the functional groups of clay humus complex. In ZT+R based treatments, lower E4/E6 ratio and total acidity of extracted HA showed higher degree of humification and stability of humic acid carbon (HA-C). The FTIR spectroscopy of the clay-humus complex (as extracted from soil) displayed the presence of a large number of functional groups in ZT+R treatment followed by ZT and CT. It was also observed that the yield of crops was also significantly higher in ZT+R than CT in both the cropping systems except in wheat crops in the M-W system. Therefore, it can be concluded that ZT+R has the potential to enrich the organic carbon (C) quality in soil and increase the aromaticity of HA, leading to carbon stabilization in soils.